2018
DOI: 10.1007/s12298-018-0611-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and yield responses of purple coneflower (Echinacea purpurea (L.) Moench) to nitrogen sources at different levels of irrigation

Abstract: Echinacea purpurea (L.) is one of the most important medicinal plants in the world showing different biochemical reactions as affected by drought stress and nitrogen fertilizer. The purpose of this study was to determine the effect of nitrogen on soluble protein, enzyme activities, carotenoids metabolism, greenness and biological yield of the Echinacea purpurea under different levels of irrigation. The experiment was conducted in a research field in Iran during 2013-2015. Irrigation treatments included irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Iron generally does not cause toxicity to plants. However, a high concentration of Fe can decrease P plant availability due to the formation of iron-phosphate salts and it is therefore harmful to plants indirectly 24 . The content of various heavy metals in all N-fertilizer types were as fallowed: Fe > Mn > Zn > Ni > Cu > Pb > Cd.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron generally does not cause toxicity to plants. However, a high concentration of Fe can decrease P plant availability due to the formation of iron-phosphate salts and it is therefore harmful to plants indirectly 24 . The content of various heavy metals in all N-fertilizer types were as fallowed: Fe > Mn > Zn > Ni > Cu > Pb > Cd.…”
Section: Resultsmentioning
confidence: 99%
“…According to Saeed et al (2018), accumulation of phenolic compounds in the plant rhizomata cum radicibus prevents NO 3 − toxicity in plants. There are some reports showing that stress conditions increase either phenylalanine ammonia lyase (PAL) synthesis or activity in plants 6,11,12,14,32 ; other authors 24 have found that some stress treatments delay the increase in wound-induced PAL activity. Phenylalanine Ammonia-Lyase activity was found to vary greatly with the stage of plant development 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was established that Echinacea purpurea for seedlings growing under irrigation conditions had a yield of raw materials on average: grasses within 4.3 -6.6 t/ha, roots 1.3 -2.2 t/ha (Table 2). [13].…”
Section: Resultsmentioning
confidence: 99%
“…E. purpurea , an Asteraceae family ornamental plant, has attracted particular interest in the phytoremediation of PAH soil contamination in the past decade [ 11 , 12 , 13 ]. E. purpurea can survive under various soil conditions and stresses, such as saline, drought, and cold, owing to its highly developed fibrous root system, strong growth, and large biomass [ 14 ]. PAH phytoremediation with E. purpurea has further advantages in revegetation cover and beautification of green spaces [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%